The Oregon Trail - Thompson, Linda, 1941- (Vero Beach, Fla. : Rourke Pub., 2005)
Examines the famous westward route of American settlement during the 1800s.
The call to go west -- Too wild and far away -- The missionaries and early followers -- The great migration -- Key people -- A timeline of the history of the Oregon Trail.
Includes bibliographical references (p. 47) and index.
Keywords: Oregon National Historic Trail -- Juvenile literature